INFLUENCE OF USING THE PAPER CUTTING AND SILIKA GEL IN PACKING ON CHARACTERISTIC OF SALAK PONDOH DURING COLD TEMPERATURE STRORAGE - T.F. Djaafar; Y Yusriani (Fakultas Pertanian, Universitas Janabadra, 2005)
This research aim is to know the change of properties of physical, chemical and organoleptic test at salak Pondoh in plastic packing and to know the packing treatment which optimally on salak use in Pondoh properties during storage. Salak Pondoh Super were in this research is 5.5 months age with quality Grade A. The Salak Pondoh Super was storage in plastic packing with three treatments i.e. 1) Addition of silica gel and paper cutting, 2) Addition of paper cutting, 3) Without addition of paper cutting and silica. All treatment were into fairish wave pasteboard which measure (20x10x10) cm, then given by treatment of convulsion during 30 minutes with frequency jolt 150/minute. The storage using low temperature (24-25oC) during 30 days. Each every 5 days were conducted on salak Pondoh properties i.e reduction sugar, total acid, vitamin C, alcohol, water contain, texture, percentage of damage and organoleptic test. The result shown that low the temperature was able decrease of Salak Pondoh damage. Addition of silica gel and paper cutting only can depress damage of salak Pondoh during 15 days. The plastic packing was able to long age storage because amount of O2 in tidiness do not equal at normal air, so that will degrade vastly of fruit respiration during 8 days. After that the salak Pondoh fruit less can be accepted by consumer in because alcohol aroma emerging. The optimally treatment in this research is addition of silica gel and paper cutting in cold temperature storage (24 - 25 OC).